1995
DOI: 10.1126/science.7792597
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of lac Repressor Core Tetramer and Its Implications for DNA Looping

Abstract: The crystal structure of the tryptic core fragment of the lac repressor of Escherichia coli (LacR) complexed with the inducer isopropyl-beta-D-thiogalactoside was determined at 2.6 A resolution. The quaternary structure consists of two dyad-symmetric dimers that are nearly parallel to each other. This structure places all four DNA binding domains of intact LacR on the same side of the tetramer, and results in a deep, V-shaped cleft between the two dimers. Each monomer contributes a carboxyl-terminal helix to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
363
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(379 citation statements)
references
References 63 publications
15
363
1
Order By: Relevance
“…3). The structure of the core tetramer does not implicate this face to be involved in tetramerization (Friedman et al 1995), and other repressors in the alignment function as dimers.…”
Section: Comparison Of Sift With Blosum62 Predictions On Laci Mutatiomentioning
confidence: 82%
“…3). The structure of the core tetramer does not implicate this face to be involved in tetramerization (Friedman et al 1995), and other repressors in the alignment function as dimers.…”
Section: Comparison Of Sift With Blosum62 Predictions On Laci Mutatiomentioning
confidence: 82%
“…2) were the only fully conserved residues in the multiple alignment of the 25 LGF proteins included in our study. Other residues in the H-T-H region ( The functional significance of some of these residues in specific members of the LGF is known and has been discussed [6,7,10,13,17]. For example, in PurR, S 14 (alignment position 22) hydrogen bonds to T17 (alignment position 25) accounting in part for the conservation of these residues.…”
Section: Multiple Alignment Of Lgf Proteinsmentioning
confidence: 99%
“…This method has recently revealed 136,149 the presence of two-looped states which is consistent with the presence of multiple configurations observed using FRET, 150,151 electron microscopy studies 152 and suggested by X-ray crystallography studies. 116 All of these experiments suggest an important role for protein flexibility. A more sophisticated technique which has been successfully applied to Gal repressor is the magnetic tweezer assay.…”
mentioning
confidence: 94%